Water Quality of Two Century old Freshwater Pond of Orai, Jalaun district Bundelkhand Region, U.P., India - Amit Pal, Jitendra Kumar (Recent Research in Science and Technology, 2010)
<span style="font-size: 12pt; font-family: ";Times New Roman";; mso-bidi-font-style: italic; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ã‚Â <span style="font-size: 12pt; font-family: ";Times New Roman";; mso-bidi-font-style: italic; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Orai is a city and a municipal board in Jalaun district in the Indian state of Uttar Pradesh. Historical Place in Orai is Mahil Talab (lake) which was constructed by Raja Mahil. Mahil Talab is located in center of the city. The physico chemical characteristic and metal concentrations were studied. Water samples were collected quarterly from ten different sites from Mahil pond during the month of November 2006 to April 2008. In cationic abundance sodium is followed by magnesium, potassium and calcium (Na> Mg > K > Ca) in pond water through out the year. The tolerance limit for TDS, SAR and % Na of water use for irrigation has been found to be fair for TDS with some exception, unsuitable for SAR and unsuitable for % Na. Nitrate, Sulphate and Phosphate were found to below the permissible limit of WHO. The presence of heavy metals followed by Mn>Pb>Fe>C>Zn>Cu>Al>Cd in the pond water throughout the year. Co, Ni and Hg were not detected in any season.